Respostas

A melhor resposta!
2014-06-02T21:34:26-03:00
X/2=y/3=z/4
(regra de 3) --> 4x=2z --- x=z/2
(regra de 3) --> 4y=3z --- y=3z/4
x+y+z=81
(substitui) --> z/2+3z/4+z=81 --- 9z/4=81 --- 9z=324 --- z= 36
x=z/2 --- x=36/2 --- x=18
y=3z/4 --- y=108/4 --- y=27

2 5 2
2014-06-02T21:57:07-03:00
  x  =  y   z , sendo x+y+z=81.
  2      3      4
1) x/2 = y/3 => x = 2y/3
2) y/3=z/4 => z = 4y/3, substituindo na expressão:
2y/3 + y + 4y/3 = 81 => 2y + 3y + 4y = 81.3 => 9y = 243 => y = 27, substituindo em 1) e 2):
...................
x = 2y/3 => x = 18;
z = 4y/3 => z = 36.
x, y e z, são respectivamente, 18, 27 e 36.
1 5 1